Probabilidade de financiamento por cartões de crédito híbridos - Ito, Marcos Kenji (2012)
Submitted by marcos ito (marcos_ito@yahoo.com.br) on 2012-01-20T18:55:07Z No. of bitstreams: 1 20120120 - MPA Marcos Kenji Ito.pdf: 931031 bytes, checksum: e54504c14f74f4f4d321823f6255eda4 (MD5) === Approved for entry into archive by Suzinei Teles Garcia Garcia (suzinei.garcia@fgv.br) on 2012-01-20T18:58:07Z (GMT) No. of bitstreams: 1 20120120 - MPA Marcos Kenji Ito.pdf: 931031 bytes, checksum: e54504c14f74f4f4d321823f6255eda4 (MD5) === Made available in DSpace on 2012-01-20T19:00:45Z (GMT). No. of bitstreams: 1 20120120 - MPA Marcos Kenji Ito.pdf: 931031 bytes, checksum: e54504c14f74f4f4d321823f6255eda4 (MD5) Previous issue date: 2011-12-20 === This research aims to identify a statistical model of propensity to revolve through store credit card, in order to maximize the credit appliance and optimize marketing efforts. The descriptive study aims to generate insights for understanding the expansion of consumer credit, in a context of lack of financing options and limitation in distribution channel. There will be a quantitative approach in the customer data base of a financial institution and through the study of socio demographic and transactional it pretends to establish a mathematical model followed by a validation of their predictive ability. === Esta pesquisa tem o objetivo de identificar as variáveis e sua influência na propensão à aquisição de crédito pessoal, propondo um modelo estatístico de propensão ao financiamento por cartões de crédito híbridos para maximização de contratação de crédito e otimização dos esforços de marketing. O estudo descritivo pode gerar insights para a compreensão da expansão do crédito ao consumo, sobretudo num contexto de escassez de opções de financiamento e limitação no canal de distribuição. Foram usados dados de uma base de clientes de uma instituição financeira com variáveis sócio demográficas e transacionai, e o modelo matemático foi seguido da validação de sua capacidade preditiva.